Novel nano-material for opto-electrochemical application - Pandey P.C.; Chauhan D.S. (My University, 2025)
We report herein the development of few types of ormosil-modified electrodes, derived from Hexacyanoferrate- [(Prussian blue systems (PB-1, PB-2, and PB-3), palladium (Pd-) system, graphite (Gr-) system, gold nanoparticle (AuNPs) system and palladium-gold nanoparticle (Pd-AuNPs)] and ruthenium bipyridyl for opto-electrochemical applications. Four approaches causing manipulation in nano-structured domains, i.e. (a) increase in the molecular size of the components generating nano-structured domains; (b) modulation via chemical reactivity; (c) modulation by non-reactive moieties and known nanoparticles; and (d) modulation by mixed approaches (a-c), all leading to decrease in a nano-structured domains; are described. The results demonstrated that an increase in the size of nano-structured domains or decrease in micro-porous geometry increases the efficiency of electro-catalysis. These ormosil-modified electrodes have been used for spectro-electrochemical measurements if encapsulated redox moieties show sharp electro-chromic behavior. Spectro-electrochemistry of few organic redox materials like tetracyanoquinodimethane (TCNQ), tetrathiafulvalene (TTF), Ferrocene including hexacyanoferrate systems are studied and reported in this communication. Typical application of these ormosil materials in electrocatalysis of hydrogen peroxide and dopamine detection are reported.